The Effect of Family Empowerment on Self-Care Motivation in Hypertension Patients: Literature Review - Agus Meriroja; Rondhianto Rondhianto; Anisah Ardiana (Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension is a common health problem among the elderly, and its management requires high self-care motivation. Family empowerment has been shown to have a significant effect on increasing self-care motivation in hypertensive patients. The purpose of this study was to analyze the effect of family empowerment on self-care motivation in hypertensive patients based on the results of a literature review. Methods: The literature study was conducted using the Sciencedirect, Pubmed, and Scopus databases, with articles published between 2018 and 2024. The keywords used included